‘No more Hoares to Paris’: British foreign policymaking and the Abyssinian Crisis, 1935 - Holt, Andrew (2011)
Italy’s invasion of Abyssinia in October 1935 prompted a major European crisis. This article applies the main theories of foreign policy analysis to the British Government’s handling of this crisis. It argues that bureaucratic politics existed, but had little impact on outcomes. Domestic politics had more influence, but did not provide detailed instructions on how to act. The perceptions of key actors, informed by reasoned judgement, determined this. Fears of the threat posed by rival states coalesced with concerns about Britain’s own military weakness, leading decision-makers to emphasise the need to act in tandem with France. British policy was therefore motivated by the tension between the public’s desire to see action against Italy and the Government’s wish to minimise any breach with her allies. These findings highlight the weaknesses of the bureaucratic politics model and show how domestic politics can affect foreign policy outcomes. They also demonstrate the interaction between rational analysis defined in terms of reasoned judgement, and actors’ perceptions. It is thus argued that benefits are to be gleaned from combining these theories.